Flap Reconstruction for Treatment of Pediatric Linear Scleroderma. Issue 5 (November 2021) - Yan, Maria; Stans, Anthony A.; Moran, Steven L.
Abstract : Background: Linear scleroderma is a rare connective tissue disease characterized by thickening of the skin due to excess collagen deposit. It is the most frequent type of localized scleroderma in the pediatric population (40%–70%), and it usually affects the extremities and head. Linear scleroderma can cause growth disturbances, extremity length discrepancy, and debilitating joint contractures. The aim of this study was to describe the surgical outcomes of microsurgical flap reconstruction of linear scleroderma in the pediatric population. Methods: A retrospective review of all children with linear scleroderma was performed at our institution. Patients less than 18 years of age with clinical diagnosis of linear scleroderma and who underwent microsurgical flap reconstruction for correction of their scleroderma were included. Fat grafting procedures were excluded. Patient demographics and surgical outcomes were collected. Results: A total 7 patients underwent microsurgical flap reconstruction for treatment of their linear scleroderma producing debilitating soft tissue contractures and preventing ambulation or elbow extension. Six patients had scleroderma involving the lower extremity and 1 involving the upper extremity. Three anterolateral thigh and 4 latissimus dorsi flaps were performed. The median age at surgery was 7 years (Q1–Q3, 5–11), and the median body mass index was 21.3 kg/m 2 (Q1–Q3, 16.5–22.1). The median follow-up was 121.1 months (Q1–Q3, 43.2–187.4). All flaps survived, and no donor site complications were reported. Perioperative complications included wound infection that required debridement (n = 1), immediate postoperative bleeding requiring surgical intervention (n = 1), intraoperative venous congestion (n = 1), and scleroderma recurrence outside the flap (n = 2). When comparing anterolateral thigh and latissimus dorsi flaps, there was no statistically significant difference in the development of surgical complications, number of surgical revisions per patient [median, 4 (Q1–Q3, 4–7) vs 2.5 (Q1–Q3, 1.3, 3), P = 0.0916], or unplanned surgical interventions [median, 0 (Q1–Q3, 0–1) vs 1 (Q1–Q3, 0–1), P = 0.7228]. The reconstruction was successful in improving range of motion in 6 patients, 5 of which reached full weight-bearing. However, all patients had residual limb deformity, and 4 had remaining extremity length discrepancy. Conclusions: Microsurgical flaps are a good option for functional improvement of severe pediatric linear scleroderma affecting the extremities. However, residual limb deformity is common, and patients are often required to undergo additional surgical revisions.